Principles of Recognizing Service Users for PPAT According to ATR/KBPN Ministerial Regulation Number 21 of 2022 - Ahsani, Muhammad Farhan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
In addition to the duties and authorities in the PPAT, there are also additional obligations that need to be known, one of which is the obligation to apply the Principle of Recognizing Service Users as a form of Prevention and Eradication of Money Laundering Crimes. In order to implement the principle of recognizing service users, PPAT is required to report all forms of financial transactions that are considered suspicious transactions carried out by service users to the Financial Transaction Reporting and Analysis Center. The writing of this journal uses normative legal research methods that refer to library materials as research materials using a statutory approach. Laws and regulations related to the theme of this journal as primary legal materials are PPAT Position Regulations, ATR/KBPN Ministerial Regulations No. 21 of 2022 and PP No. 43 of 2015, secondary legal materials in the form of research results, journals and theories related to discussions in this journal journals and tertiary legal materials in the form of electronic media and legal dictionaries. ATR/KBPN Ministerial Regulation Number 21 of 2022 requires PPAT to exercise additional authority, namely by implementing the principle of recognizing service users other than those specified by the PPAT Position Regulation. PPAT is mandatory to apply the principle of recognizing service users, because PPAT is one of the professions that must report based on Article 3 of PP No. 43 of 2015 for the Prevention and Eradication of Money Laundering. Based on the discussion, a conclusion was produced stating that the application of the principle of recognizing service users is not related to the authority of PPAT in making an authentic deed but binds the authority of PPAT obtained by attribution. This is because in the application of the principle of recognizing PPAT service users, they are asked to explore information in the form of service user identity and the acquisition of sources of funds which will later be reported to PPATK.